2020
DOI: 10.14744/tjtes.2020.12544
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Demographic and Clinical Features of Pregnant and Non-pregnant Patients Undergoing Appendectomy

Abstract: BACKGROUND: This retrospective study aims to compare the demographic and clinicopathological characteristics of the pregnant and non-pregnant patients who underwent appendectomy with a presumed diagnosis of acute appendicitis. METHODS:Between June 2009 and January 2019, 431 reproductive-aged of female patients underwent appendectomy with a presumed diagnosis of acute appendicitis. Patients were divided into two groups considering their pregnancy status: pregnant group (n=48) and non-pregnant group (n=383). Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Some studies have shown that inflammatory factors (such as IL-6, IL-8, CD44, etc.) are helpful for diagnosis of AA (24), and WBCC and CRP are certainly the most widely used (1,25). At the same time, this study increased NE% for analysis.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies have shown that inflammatory factors (such as IL-6, IL-8, CD44, etc.) are helpful for diagnosis of AA (24), and WBCC and CRP are certainly the most widely used (1,25). At the same time, this study increased NE% for analysis.…”
Section: Discussionmentioning
confidence: 65%
“…1). After title/abstract and full-text screening, 114 articles 24137 were included in the systematic review and 100 articles 2447,4951,5358,6066,68–72,7489,91105,108118,121,123127,129134,136,137 were included in the meta-analysis for either fetal loss, preterm birth, or maternal mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In our series, four patients out of eight were in their second trimester, similarly to others who reported the second trimester as the most frequent months to have AA [ 8 10 ]. Others stated the first trimester as the most common [ 11 , 12 ]. A Swedish study linked reduced numbers of AA in the 3 rd trimester to positive effects of hormones and TH1-mediated inflammatory response [ 13 ].…”
Section: Discussionmentioning
confidence: 99%